Role of DOSE Escalation in whole Brain Radiotherapy for Brain Metastasis in Patients with a Favorable Survival Prognosis - Saroj Dhaka; Anil Rajani; Rakesh Sihag; Rajesh Kumar; Shankar Lal Jakhar (Asian Pacific Journal of Cancer Care, 2022)
Background: Brain metastases is a major health care problem and is the most common intracranial cancer in adults. These patients may benefit from intensive treatments including neurosurgery and radiosurgery but many patients cannot receive such treatment, and whole brain radiotherapy (WBRT) alone is the only option. The most common WBRT schedule is 30 Grays (Gy) in 10 fractions (fr). However there is need to develop fractionation schedules, but total dose still remain dilemma.The Purpose of this study to assess the potential benefit of dose escalation beyond 30 Gy. Patients and methods: Total 120 patients with multiple brain metastases, previously untreated with WBRT were randomly assigned into two arms. All patients have favorable survival prognosis. Seventy patients received a total 30Gy in 10fr, 3Gy/fr administered daily 5days/week in arm A and 50 patients received 39Gy in 13fr, with same schedule in arm B. Both arms were compared for local control (LC) and overall survival (OS). Results: The LC rate at 18 months was 11% after 30 Gy and 24% after 39 Gy (p value=0.068). The survival rate at18 months was 21% after 30 Gy and 38% after 39Gy (OS 21% vs. 38%, hazard ratio 0.593; 95% CI: .395-.891; p value=0.047). On subgroup analysis of primary tumor, the 18 months LC rate was 16% vs 53% in Breast (p value=0.020) and10% vs 11% in Lung cancer (p value=0.809) in arm A and B respectively; the 18 months OS rate was 14% vs26% in Lung (P value=0.160) and 37% vs 73% in Brest cancer (p value=0.034) in arm A and B respectively. Conclusion: Escalation of the WBRT dose beyond 30 Gy resulted in better outcomes, particularly for patients with primary breast cancer.